Research on Leisure Sports Consumption among the Chinese Masses: A Case Study of Yibin City, Sichuan Province, China: Leisure Sports Consumption - Li, Yan (Quality in Sport, 2025)
This study explores the impact of the new economy on residents' leisure sports consumption. Taking residents in the Xiajiangbei area of Yibin City in China as the research subjects, 190 residents were randomly selected for a questionnaire survey, and descriptive statistical analysis was used to process the data. The results show that: under the influence of the "new economy," residents' income levels have improved to some extent, but the leisure sports consumption level of those without a stable income remains significantly low. Additionally, a lack of consumption awareness and outdated perceptions are key factors restricting residents' engagement in leisure sports activities. The quantity, quality, and allocation of local sports facilities are objective conditions affecting residents' effective participation in leisure sports consumption. In conclusion, the leisure sports consumption level of residents in the Lingang area is not high. Enhancing residents' awareness of sports consumption, further increasing income levels, and improving facility conditions are critical measures to promote their leisure sports consumption.